2021
DOI: 10.1038/s41598-021-99063-9
|View full text |Cite
|
Sign up to set email alerts
|

Integrative transcriptomic and gene co-expression network analysis of host responses upon Verticillium dahliae infection in Gossypium hirsutum

Abstract: Worldwide, Verticillium wilt is among the major harmful diseases in cotton production, causing substantial reduction in yields. While this disease has been extensively researched at the molecular level of the pathogen, the molecular basis of V. dahliae host response association is yet to be thoroughly investigated. In this study, RNA-seq analysis was carried out on V. dahliae infected two Gossypium hirsutum L. cultivars, Xinluzao-36 (susceptible) and Zhongzhimian-2 (disease resistant) for 0 h, 24 h, 72 h and 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 72 publications
0
19
0
Order By: Relevance
“…The pathogenic mechanism of V. dahliae includes two theories, one of which is vascular bundle blockage theory (Ma et al, 2021). Studies have shown that V. dahliae has more enzymatic genes that degrade cell walls than other plant pathogenic fungi (Jeffress et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The pathogenic mechanism of V. dahliae includes two theories, one of which is vascular bundle blockage theory (Ma et al, 2021). Studies have shown that V. dahliae has more enzymatic genes that degrade cell walls than other plant pathogenic fungi (Jeffress et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Due to the stable dormant structure microsclerotia, longterm variability, and coevolution with host plants (Ju et al, 2020;Höfer et al, 2021;Starke et al, 2021), controlling the spread of Verticillium wilt in plants remains challenging using currently available methods, such as chemical control, genetic breeding, and optimization of the cropping pattern (Ostos et al, 2020;Ramirez-Gil and Morales-Osorio, 2021;Zhang Y. L. et al, 2021). Disease resistance breeding is limited by a long breeding cycle and a lack of natural resistance resources, and chemical control has no beneficial effect on the control of soil-borne diseases (Diaz-Rueda et al, 2021;Hanika et al, 2021;Sunico et al, 2022).…”
Section: Antifungal Effects Of Volatile Organic Compounds Produced By...mentioning
confidence: 99%
See 1 more Smart Citation
“…However, few studies have focused on the use of extreme cotton fiber material in backcross populations to study elongation. In addition, Weighted gene coexpression network analysis (WGCNA) is very quick and efficient for mining functionally relevant genes in coexpression modules, and it has been widely used in a variety of crops to mine the corresponding candidate genes [ 77 , 78 , 79 , 80 ].…”
Section: Introductionmentioning
confidence: 99%
“…RNA-seq has been widely applied to monitor the gene expression profiles and describe the response characteristics of cotton roots under V. dahliae infection [ 17 , 28 , 29 , 30 , 31 , 32 ], and has a great potential to enrich our understanding of how cotton has elaborated various defense mechanisms against pathogen attacks. Therefore, in the current work, we conducted RNA-seq to discover the genes expressed in the roots of Gossypium hirsutum resistant cultivar Liaomian No.…”
Section: Introductionmentioning
confidence: 99%